Pedagogical Challenges in the Teaching and Learning of Oral Skills in English in Secondary Schools in Kenya - Abiero, Damaris Auma; Ajowi, Jack Odongo; Ondondo, Emily Ayieta (International Journal of Novel Research in Humanity and Social Sciences, 2019)
Oral skills in English are taught and examined in Kenyan secondary schools with the purpose of developing fluency and accuracy in speech communication. However, majority of students do not attain intelligibility at the close of their study. Oral skills are examined in paper one of the English language exam though in written form. In 2016 the students scored a mean of 29.15 in the paper. In 2017, the students scored 25.89 indicating a decline of 3.26 points. This shows that not many secondary school students in Kenya are competent in oral skills in the English language. English is a second language to Kenyan students after their mother tongue. They develop its competence through learning it in the classroom context. The objective of the study was to determine the pedagogical challenges involved in the teaching and learning of content of oral skills. The study attempted to explain the challenges involved in teaching and learning of oral skills in English language which could be of help to curriculum developers, teachers of English, students and future researchers. The study was confined to the pedagogical challenges that are involved in the teaching and learning of oral skills in English in relation to teaching content, teaching construct and teaching context. The theoretical framework on which the study was based was the socio-cultural- constructivism theory. This theory is relevant to the acquisition of oral skills in the classroom where both the teacher and the learner actively participate in the learning process. The study was done in Kisumu East Sub- county with a population of 4021 students and 47 teachers of English. Data was collected from 295 students and 35 teachers a total of 330 participants through the use of Krejcie & Morgan (1970) table of determining sample. The study employed concurrent triangulation design with mixed methods approach. Questionnaires, unstructured interview schedules and observation schedules were used to collect and analyze data concurrently. The quantitative data was summarized using descriptive statistics and presented using tables, pie charts and bar graphs while qualitative data was put under themes and presented in verbatim and narratives. Analyzed data were then merged for presentation and discussions. The study established that there were pedagogical challenges in the teaching and learning of oral skills in English in relation to teaching content, teaching construct and teaching context. The study therefore recommended that the curriculum developers need to come up with comprehensive teaching and learning materials that would help both the teachers and the students to succeed in teaching and learning content of oral skills in English. Textbooks should be more comprehensive in oral drills exercises. English aural exams should be introduced in the curriculum as done in other foreign languages like French and Germany. All the stakeholders should be committed and work together for the success of oral skills acquisition in school.
Keywords: Pedagogical Challenges; Oral Skills in English.